Lower Extremity Injury After Return to Sports From Concussion: A Systematic Review. Issue 1 (27th January 2022) - Jildeh, Toufic R.; Castle, Joshua P.; Buckley, Patrick J.; Abbas, Muhammad J.; Hegde, Yash; Okoroha, Kelechi R.
Background: Recent studies have suggested increased rates of lower extremity (LE) musculoskeletal injury after a diagnosed concussion, although significant heterogeneity exists. Purpose: To examine the current body of research and determine whether there is an increased risk for LE musculoskeletal injury after a concussion and to identify populations at an increased risk. Study Design: Systematic review; Level of evidence, 3. Methods: A systematic review of current literature using MEDLINE and PubMed databases was performed. Keywords included concussion, athlete, lower extremity injury, and return to sport . Inclusion criteria required original research articles written in the English language examining the rate of LE injuries after a diagnosed concussion. Results: A total of 13 studies involving 4349 athletes (88.1% male and 11.9% female; mean age, 19.8 years) met inclusion criteria. Athletes were classified as high school (46.1%), collegiate (17.0%), or professional (36.9%). Of the 13 studies, 4 demonstrated an increased risk of LE injury within 90 days of a diagnosed concussion (odds ratio [OR], 3.44; 95% CI, 2.99-4.42), and 6 revealed an elevated risk of injury within 1 year of concussion (OR, 1.85; 95% CI, 1.73-2.84). Increased risk was seen in professional (OR, 2.49; 95% CI, 2.40-2.72) and collegiate (OR, 2.00; 95% CI, 1.96-2.16) athletes compared with high school athletes (OR, 0.97; 95% CI, 0.89-1.05). A stepwise increase in risk of sustaining an LE injury was observed with multiple concussions, with increasing risk observed from ≥2 (OR, 2.29; 95% CI, 1.85-2.83) to ≥3 (OR, 2.86; 95% CI, 2.36-3.48) career concussions. Conclusion: An increased incidence of LE injuries was observed at 90 days and 1 year after the diagnosis of a concussion. Higher levels of competition, such as at the collegiate and professional levels, resulted in an increased risk of sustaining a subsequent LE injury after a diagnosed concussion. These results suggest an at-risk population who may benefit from injury prevention methods after a concussion. Future studies should focus on identifying which injuries are most common, during what time period athletes are most vulnerable, and methods to prevent injury after return to sports.